1990
DOI: 10.1016/0753-3322(90)90077-m
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxides and atherosclerosis

Abstract: Plasma lipid peroxide concentrations were measured in 100 patients with occlusive arterial disease proved angiographically (50 patients with ischaemic heart disease, 50 with peripheral arterial disease) and compared with values in 75 control patients with no clinical evidence of atherosclerosis. Lipid peroxide concentrations were significantly higher in patients both with ischaemic heart disease (median 4-37 iimol/l (interquartile range 3-85-5-75 [tmol/l); p<0-001) and with peripheral arterial disease (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 2 publications
4
33
0
Order By: Relevance
“…Diene conjugates in serum were also increased in these patients (Table 1). These results are in accordance with other studies (Uzel et al 1987;Ga/Iou et al 1993;Stringer et al 1989;Loeper et al 1991). However, in this study, the susceptibility of serum to copper-induced lipid peroxidation were found unchanged in diabetes and myocard infarction comparing healthy subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Diene conjugates in serum were also increased in these patients (Table 1). These results are in accordance with other studies (Uzel et al 1987;Ga/Iou et al 1993;Stringer et al 1989;Loeper et al 1991). However, in this study, the susceptibility of serum to copper-induced lipid peroxidation were found unchanged in diabetes and myocard infarction comparing healthy subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the tissue damage is consider to be mediated by these free radicals by attacking membranes through peroxidation of unsaturated fatty acids (Stringer et al, 1989). In the present study the concentrations of lipid peroxides were increased in diabetic rats, which caused the development of diabetes, indicating an increase in the generation of free radicals.…”
Section: Discussionmentioning
confidence: 94%
“…At least six case-control studies on vitamin E and CVD risk were published (79,81,82,(96)(97)(98)(99). They were small in size (n = 1,846) and their results did not agree (OR, 0.88; 95% CI, 0.70 to 1.09).…”
Section: Vitamin Ementioning
confidence: 89%